Adaptasi instrumen social appearance anxiety scale (SAAS) pada individu dewasa awal - Pramuditha, Livina Intania; Ilmi, Lu'luin Nuzulul; Choiria, Luluk (Jurnal Psikologi Poseidon, 2026)
Scales measuring anxiety have been extensively studied in Indonesia; however, research on social appearance anxiety in the Indonesian context remains scarce. Social appearance anxiety is the anxiety that arises from the fear of being negatively evaluated by others regarding one’s physical appearance. The limited discussion regarding such measurement tools indicates a need for a valid and reliable instrument. The measurement tool that can be used to assess this anxiety is the Social Appearance Anxiety Scale, which consists of 16 items. The purpose of this study is to adapt and test the validity and reliability of this measurement tool so that it can be used in the Indonesian context. This study involved 320 participants meeting the criteria of being women over 18 years of age and unmarried. Analysis using the Jamovi software revealed that the model did not yet fit well, necessitating modifications through item elimination. The results of the modifications showed a TLI parameter of 0.905 and a CFI of 0.905 in the model fit. Additionally, the RMSEA was 0.106, a value that still falls within the category of not achieving model fit. Thus, this measurement tool has the potential for use in Indonesia but requires revisions to several items.